2020
DOI: 10.35848/1347-4065/ab6b7c
|View full text |Cite
|
Sign up to set email alerts
|

NiSi2 as a bottom electrode for enhanced endurance of ferroelectric Y-doped HfO2 thin films

Abstract: We exploit the uniform silicidation of an ultra-thin Ni film deposited on crystalline silicon that upon rapid thermal annealing transforms into NiSi 2 and then is used as a bottom electrode (BE) with the right structure for orthorhombic crystallization of Y-doped HfO 2 (YHO) during an additional post deposition annealing (PDA) process. Compared to a standard TiN BE in metal-insulator-metal structures, the use of NiSi 2 and PDA promotes a more reproducible and stable ferroelectric behavior of YHO thin films. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Oxygen vacancies have also been identified as the main factor behind the deleterious wake-up effect [28,29], i.e. the increase in remanent polarization with electric field cycling, as well as assisting in fatigue and eventual dielectric breakdown [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen vacancies have also been identified as the main factor behind the deleterious wake-up effect [28,29], i.e. the increase in remanent polarization with electric field cycling, as well as assisting in fatigue and eventual dielectric breakdown [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Pešic´et al suggested that the fastest O vacancy defect generation occurs at the TiO x interface between HfO 2 and TiN where electron trapping creates leakage pathways and eventually results in a breakdown of the device [29]. While the inclusion of oxygen vacancies in small concentration can be favorable for eliciting the ferroelectric phase in HfO 2 , excess vacancy formation from TiN can negatively impact the endurance of HfO 2 ferroelectric devices [30,42].…”
Section: Introductionmentioning
confidence: 99%